Photocatalytic degradation and removal mechanism of ibuprofen via monoclinic BiVO4 under simulated solar light. (May 2016) - Li, Fuhua; Kang, Yapu; Chen, Min; Liu, Guoguang; Lv, Wenying; Yao, Kun; Chen, Ping; Huang, Haoping
Abstract: Characterized as by X-ray diffraction, scanning electron microscopy and UV–vis diffuse reflectance spectra techniques, BiVO4 photocatalyst was hydrothermally synthesized. The photocatalytic degradation mechanisms of ibuprofen (IBP) were evaluated in aqueous media via BiVO4 . Results demonstrated that the prepared photocatalyst corresponded to phase-pure monoclinic scheelite BiVO4 . The synthesized BiVO4 showed superior photocatalytic properties under the irradiation of visible-light. The photocatalytic degradation rate of IBP decreased with an increase in the initial IBP concentration. The degradation process followed first-order kinetics model. At an IBP concentration of 10 mg L −1, while a BiVO4 concentration of 5.0 g L −1 with pH value of 4.5, the rate of IBP degradation was obtained as 90% after 25 min. The photocatalytic degradation of IBP was primarily accomplished via the generation of superoxide radical ( O 2 − ) and hydroxyl radicals ( OH). During the process of degradation, part of the OH was converted from the O 2 − . The direct oxidation of holes (h + ) made a minimal contribution to the degradation of IBP. Graphical abstract: Highlights: Synthesis and characterization of monoclinic BiVO4 . Photocatalytic activity for degradation of ibuprofen under simulated solar light. Effect of operational parameters on the photocatalytic degradation of ibuprofen. Removal mechanism of ibuprofen via monoclinic BiVO4 under simulated solar light.